2017
DOI: 10.1177/1359105317692142
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of psychosocial factors and their relationship to impairment and functionality in multiple sclerosis

Abstract: The stress effect on multiple sclerosis remains unclear. Moderating psychosocial factors may be involved. This study compares some of them in people with multiple sclerosis and healthy controls, and their association with disease parameters. Coping style, social support, anxiety, alexithymia and early-life stress were measured, along with impairment and functionality. People with multiple sclerosis scored significantly higher on anxiety, alexithymia, and avoidance and instinctive coping but lower in social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…The findings indicate a statistically not significant main effect, which means that ACEs are not significantly associated with ADs in adulthood. These results are consistent with previous studies that underscore that early-life stress seems not to have an important role in ADs such as multiple sclerosis (Briones-Buixassa et al, 2019) or systemic rheumatic diseases (Luiz et al, 2018).…”
Section: Summary Of Findings and Theoretical Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…The findings indicate a statistically not significant main effect, which means that ACEs are not significantly associated with ADs in adulthood. These results are consistent with previous studies that underscore that early-life stress seems not to have an important role in ADs such as multiple sclerosis (Briones-Buixassa et al, 2019) or systemic rheumatic diseases (Luiz et al, 2018).…”
Section: Summary Of Findings and Theoretical Implicationssupporting
confidence: 93%
“…Moreover, autoimmune patients with histories of childhood trauma have increased relapse rates and reduced treatment response compared with patients without early-life trauma (Spitzer et al, 2012). On the other hand, recent studies have yielded contradictory results, revealing no relationship between stressful events and the risk for the onset and exacerbation of some ADs (Briones-Buixassa et al, 2019;Luiz et al, 2018). Authors propose other moderating psychosocial factors, such as how people deal with stress, family cohesion, child dispositional attributes, or external support, because traumatic stress does not directly affect health.…”
mentioning
confidence: 99%
“…Over two years, the respondents experienced highly stressful situations much more often than healthy individuals and used coping strategies focused on emotions and avoidance more often, making their psychophysical state deteriorate. A study among multiple sclerosis patients showed similar dependencies (Briones-Buixassa et al, 2019).…”
Section: Quality Of Life and Resources Among Those At Risk Of Exclusionmentioning
confidence: 90%
“…Using maladaptative coping strategies can have health, psychological, and social consequences. In a Spanish study among multiple sclerosis patients (Briones-Buixassa et al, 2019), it was demonstrated that the patients, compared to the group of healthy people, used more strategies such as avoidance and instinctive action and showed fewer social joining attitudes.…”
Section: Cor Approach To Copingmentioning
confidence: 99%
“…Klinische Daten zeigten jedoch bei MS Patienten im Vergleich zu gesunden Probanden höhere Testwerte in Bezug auf Angststörungen, Alexithymie, Vermeidungsverhalten, instinktiven Copingstrategien und niedrigere in Bezug auf sozialen Rückhalt [158].…”
Section: Prävalenz Der Alexithymie Bei Multipler Skleroseunclassified